(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
The goal of the project is to study the scanning electron microscope and give a general idea about the electron microscope and the stages of its development and know the mechanism on which it works, as well as knowing the basic components of the microscope and the mechanism of operation of each part. The project also aims to study the defects and distortions that appear on the image as a result of distortions due to mechanical or operational defects. In the microscope.We conclude in this research that some preventive and safety measures must be taken when operating these devices. When these devices operate, they produce X-rays when electrons collide with the sample. As we know, X-rays are harmful to humans, but you should not worry about exposure to these It is completely insulated and the generated.